Exploring the potential of Lactobacillus and Saccharomyces for biofunctionalities and the release of bioactive peptides from whey protein fermentate. (August 2022) - Dineshbhai, Chopada Kevalkumar; Basaiawmoit, Bethsheba; Sakure, Amar A.; Maurya, Ruchika; Bishnoi, Mahendra; Kondepudi, Kanthi Kiran; Patil, G.B.; Mankad, Maunil; Liu, Zhenbin; Hati, Subrota
Abstract: Whey protein concentrate-80 (WPC-80) fermented with L. fermentum (KGL4) (37 °C) and S. cerevisiae (WBS2A) (25 °C) was tested for ACE-inhibitory and antioxidant activities over different periods (12, 24, 36 and 48 h). Proteolytic activity (OPA method) was used to optimize the growth conditions (inoculation rate, i.e. at 1.5%, 2.0%, and 2.5% and incubation time, i.e. 12, 24, 36, and 48 h) for peptide production. Results indicated that the highest amount of peptides was obtained at 7.24 mg/mL for KGL4 (37 °C, 48 h) and 8.59 mg/mL for WBS2A (25 °C, 48 h). The whey protein fermentate inhibited the LPS-induced NO production, while enhanced production concentrations of TNF-α, IL-6, and IL-1β. Subsequently, SDS-PAGE, as well as Two-Dimensional (2D) gel electrophoresis methods, were applied for protein purification using water-soluble extracts (WSEs) of WPC-80 fermented by a combination of L. fermentum and S. cerevisiae . On SDS-PAGE, protein bands were observed in the range of 10–55 kDa, whereas on the 2D page, protein spots were in the range of 10–70 kDa. All the 2D spots were analyzed using RPLC/MS. WSEs of 3 kDa and 10 kDa permeates were used in RP-HPLC to identify distinct peptide fractions. The data from LC/MS was also characterized by utilizing ProteinPilot software. Further, different functional groups were also analyzed using FTIR investigation. The research aims to isolate and characterize novel ACE-inhibitory and antioxidative peptides from fermented WPC-80 produced by Lactobacillus fermentum and S. cerevisiae . Graphical abstract: Image 1 Highlights: Whey protein concentrate (WPC) was fermented with Lactobacillus as well as yeast. Yeast-lactic fermented whey protein produced ACE-inhibitory, antioxidative and anti-inflammatory activities. Whey protein fermented with Lactobacillus and Saccharomyces produce peptides. Antioxidative and anti-hypertensive peptides were identified from fermented WPC. It could be a better source for the Anti-oxidative and anti-hypertensive peptides.